Web-Based Equipment Management System - Azmi, Atira (IRC, 2019)
Inventory management is considered as a major concern in Honda Malaysia Sdn.Bhd. In Honda Malaysia Sdn.Bhd, Equipment Section had a difficulty in their inventory process such as unorganized document, problems with inventory arrangement for their stock, and they need a systematic system to manage their stock. Because of these problems, they may have inaccurate records balance stock due to abnormal issues. Equipment Section need to have a management system in order to ease their daily process. Based on research of this problem aim to create Web Based Equipment Management System in Material Service 2 Department. The most importantly function in the system is to find balance stock that will fulfill the customer demand and avoiding overstocks or low stocks because of abnormal issues. Additionally, all progress done by equipment section will be updated in the system. The objectives of this research are to transform from update inventory data using a manual method into system based, make data accessible through live systems by using a server, and all document are standardization in the system. Digitizing document is the process of converting information into digital format such as from paper into system based. In order to achieve the aim and objectives of the study, the comprehensive review of literature and test case were carried out. Subsequently, it is hoped that by providing the Web Based Equipment Management System can improve work efficiency, all data is sharing through system and more security where only authorized person can manage data in the system. This system is written in C#, VB.Net and ASP. Net. System usability testing and user acceptance testing have been done in order to make sure Web-Based Equipment Management System meet the user requirements.